Recent advances in cellular optogenetics for photomedicine - Chen, Bing; Cui, Meihui; Wang, Yuan; Shi, Peng; Wang, Hanjie; Wang, Feng (Advanced drug delivery reviews, 2022)
[Display omitted] Since the successful introduction of exogenous photosensitive proteins, channelrhodopsin, to neurons, optogenetics has enabled substantial understanding of profound brain function by selectively manipulating neural circuits. In an optogenetic system, optical stimulation can be precisely delivered to brain tissue to achieve regulation of cellular electrical activity with unprecedented spatio-temporal resolution in living organisms. In recent years, the development of various optical actuators and novel light-delivery techniques has greatly expanded the scope of optogenetics, enabling the control of other signal pathways in non-neuronal cells for different biomedical applications, such as phototherapy and immunotherapy. This review focuses on the recent advances in optogenetic regulation of cellular activities for photomedicine. We discuss emerging optogenetic tools and light-delivery platforms, along with a survey of optogenetic execution in mammalian and microbial cells.